Investigation of the ST131 Clone by Real-Time PCR in Escherichia coli Strains Isolated in Patients from Intensive Care Units and Other Services - Hasli, Figen; Bilgin, Kemal; Kadi, Hamza; Cayci, Yeliz Tanriverdi; Birinci, Asuman (Galenos Publ House, 2023)
Introduction: The prevalence and spread rate of the Escherichia coli ST131 clone continue to be an important issue requiring investigation. This study investigated the presence of the ST131 clone in E. coli isolates isolated from intensive care units (ICUs) and other services using real-time Materials and Methods: A total of 200 E. coli isolates were included in the study. The double-disk synergy method was used to show the presence of extended-spectrum beta-lactamases (ESBL). The ST131 clones were investigated using the real-time PCR method in all isolates. Results: E. coli ST131 clones were identified in 17 of 100 strains isolated from the specimens from ICUs. Of these strains, 15 (29.4%) of the 51 ESBL positive isolates and two (4.1%) of the 49 ESBL negative isolates were identified as E. coli ST131 clones. E. coli ST131 clones were identified in 13 of 100 strains isolated from non-ICUs. Among these strains, 12 (34.3%) of 35 ESBL positive isolates and one (1.5%) of the 65 ESBL negative isolates were identified as E. coli ST131 clones. Conclusion: While the E. coli ST131 clone was common in ESBL-producing isolates, its presence did not differ in intensive or non-ICUs.
Keywords: E. coli; ST131; Intensive Care Unit